Deciphering the causal link between gut microbiota and membranous nephropathy: insights into potential inflammatory mechanisms - Jianbo Qing; Changqun Li; Nan Jiao (Renal Failure)
Background Membranous nephropathy (MN), a leading cause of adult nephrotic syndrome and renal failure, has been linked to gut microbiota (GM) and their metabolites. However, direct causal relationships and therapeutic implications remain unclear.Methods We utilized a comprehensive GWAS dataset that encompasses GM, metabolites, and MN through two-sample Mendelian randomization (MR) analyses, bidirectional MR evaluations, and detailed sensitivity tests.Results We identified strong causal associations between nine specific types of GM, including class Clostridia (OR = 1.816, 95%CI: 1.021–3.236, p = .042), class Melainabacteria (OR = 0.661, 95%CI: 0.439–0.996, p = .048), order Gastranaerophilales (OR = 0.689, 95%CI: 0.480–0.996, p = .044), genus Alistipes (OR = 0.480, 95%CI: 0.223–0.998, p = .049), genus Butyricicoccus (OR = 0.464, 95%CI: 0.216–0.995, p = .048), genus Butyrivibrio (OR = 0.799, 95%CI: 0.639–0.998, p = .048), genus Ruminococcaceae UCG003 (OR = 0.563, 95%CI: 0.362–0.877, p = .011), genus Streptococcus (OR = 0.619, 95%CI: 0.393–0.973, p = .038), and genus Oscillibacter (OR = 1.90, 95%CI: 1.06–3.40, p = .031). Additionally, the metabolite tryptophan also exhibited a significant causal influence on MN (OR = 0.852, 95%CI: 0.754–0.963, p = .010). Sensitivity and reverse MR analyses confirmed the robustness of these findings. Further exploration using gutMGene database suggests that GM may influence MN by affecting the release of inflammatory factors and modulating inflammatory pathways.Conclusion This study offers a comprehensive understanding of the causal links between GM, their metabolites, and MN, which highlight potential pathways for developing new preventive and therapeutic strategies for this condition.